2023
DOI: 10.1094/mpmi-06-23-0078-r
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PWT7, Located on a Supernumerary Chromosome, Is Associated with Parasitic Specialization of Pyricularia oryzae on Wheat

Abstract: Pyricularia oryzae, a blast fungus of gramineous plants, is composed of various host-genus specific pathotypes. The avirulence of an Avena isolate on wheat is conditioned by PWT3 and PWT4. We isolated the third avirulence gene from the Avena isolate and designated it as PWT7. PWT7 was effective as an avirulence gene only at the seedling stage or on leaves. PWT7 homologs were widely distributed in a subpopulation of the Eleusine pathotype and the Lolium pathotype but completely absent in the Triticum pathotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Genetic analysis of crosses between isolates from different host‐specific lineages have demonstrated that the incompatibility of P. oryzae on nonhost species is in most cases controlled by relatively few genes, generally one to three (Cruz & Valent, 2017 ; Murakami et al., 2003 ; Takabayashi et al., 2002 ; Tosa et al., 2006 ; Valent & Chumley, 1991 ). Several of these genes code for effector proteins such as PWL1 and PWL2 that control pathogenicity towards Eragrostis curvula (weeping lovegrass) or PWT3, PWT4 or PWT7 that control pathogenicity on wheat (Asuke et al., 2023 ; Inoue et al., 2017 ; Sweigard et al., 1995 ). In all studied cases, it was the loss‐of‐function alleles that conferred compatibility on the new host, suggesting that the host specificity of the blast fungus is frequently determined by immune receptor‐mediated detection of virulence effectors in nonhost plants.…”
Section: Taxonomy Host Range and The Population Structurementioning
confidence: 99%
“…Genetic analysis of crosses between isolates from different host‐specific lineages have demonstrated that the incompatibility of P. oryzae on nonhost species is in most cases controlled by relatively few genes, generally one to three (Cruz & Valent, 2017 ; Murakami et al., 2003 ; Takabayashi et al., 2002 ; Tosa et al., 2006 ; Valent & Chumley, 1991 ). Several of these genes code for effector proteins such as PWL1 and PWL2 that control pathogenicity towards Eragrostis curvula (weeping lovegrass) or PWT3, PWT4 or PWT7 that control pathogenicity on wheat (Asuke et al., 2023 ; Inoue et al., 2017 ; Sweigard et al., 1995 ). In all studied cases, it was the loss‐of‐function alleles that conferred compatibility on the new host, suggesting that the host specificity of the blast fungus is frequently determined by immune receptor‐mediated detection of virulence effectors in nonhost plants.…”
Section: Taxonomy Host Range and The Population Structurementioning
confidence: 99%
“…The evolutionary history of WB yields new insights in this regard by building on foundational work from Tosa and colleagues who identified five PWT genes that determine P. oryzae avirulence on wheat 33,37,50 . After surveying allele distributions for two cloned genes, they proposed an evolutionary model where functional losses of PWT6 and currently unknown PWT genes allowed an Eleusine pathogen to colonize rwt3 wheat, probably via an intermediate Lolium host 32 .…”
Section: Articlementioning
confidence: 99%
“…While these instances highlight HGT as a possible driver of genetic variation in the blast fungus, the exact mechanisms facilitating HGT remain unclear. In addition to gene transfer, mChr have been associated with virulence gene reshuffling and recombination with core chromosomes (Kusaba et al 2014;Peng et al 2019;Langner et al 2021;Asuke et al 2023;Gyawali et al 2023), indicating that horizontal mChr transfer could be instrumental in driving genomic innovation. In this study, we provide evidence for multiple horizontal mini-chromosome transfer events involving clonal lineages of the rice blast fungus M. oryzae that occurred under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptive role of mChr in plant pathogenic fungi is underpinned by their correlation to virulence in various pathogen-host systems (Miao et al 1991; Kistler 1996; Han et al 2001; Akagi et al 2009; Ma et al 2010; Chuma et al 2011; Balesdent et al 2013; van Dam et al 2017; Habig et al 2017; Bhadauria et al 2019; Henry et al 2021; Asuke et al 2023). In addition, variation in virulence has been partly attributed to the horizontal transfer of mChr (Mehrabi et al 2011).…”
Section: Introductionmentioning
confidence: 99%